Geographical distribution of natural gas manufacturing in Basrah Province - Ayoub Yaqoub Yousef Al-khalidi, Fatima; Attia Abdul Hussein Al-Jourani , Assist. Prof. Dr. Hamid (Basra studies journal, 2023)
The natural gas industry globally has witnessed great developments by all standards over the past years, in addition to the entry of natural gas into the field of industry as a fuel for electric power stations or as a raw material for fertilizer and petrochemical companies and others. Thus, the province of Basra has drawn the attention of students due to the great gas wealth it contains represented by the giant oil fields from which natural gas is extracted, accompanied with oil or free, as in the Siba field. Production began to increase since 1970 after entering various industries in the governorate as fuel or as a raw material and trying to reduce gas burning and waste through the entry of foreign companies into the oil licensing rounds through participation contracts, such as the entry of Shell Company equally in production with the South Gas Company and an attempt to reduce waste from Burning gas to reduce economic losses.